Accumulation of advanced glycation end products in follicles is associated with poor oocyte developmental competence. (24th August 2019) - Takahashi, Nozomi; Harada, Miyuki; Azhary, Jerilee M K; Kunitomi, Chisato; Nose, Emi; Terao, Hiromi; Koike, Hiroshi; Wada-Hiraike, Osamu; Hirata, Tetsuya; Hirota, Yasushi; Koga, Kaori; Fujii, Tomoyuki; et al.
Abstract: Advanced glycation end products (AGEs) affect the follicular microenvironment. The close relationship between AGEs, proinflammatory cytokine production and activation of the unfolded protein response (UPR), which involves activating transcription factor 4 (ATF4), is crucial for regulation of various cellular functions. We examined whether accumulation of AGEs in follicles was associated with proinflammatory cytokine production and activation of the UPR in granulosa cells and decreased oocyte developmental competence. Concentrations of AGEs, soluble receptor for AGE (sRAGE), interleukin (IL)-6 and IL-8 in follicular fluid (FF) were examined by ELISAs in 50 follicles. mRNA expression of ATF4, IL-6 and IL-8 in cumulus cells (CCs) were examined by quantitative RT-PCR in 77 samples. Cultured human granulosa-lutein cells (GLCs) were treated with AGE-bovine serum albumin (BSA) alone or following transfection of ATF4-targeting small interfering RNA. The AGE concentration and the AGE/sRAGE ratio in FF were significantly higher in follicles containing oocytes that developed into poor-morphology embryos (group I) than those with good-morphology embryos (group II). When compared with sibling follicles from the same patients, the AGE/sRAGE and concentrations of IL-6 and IL-8 in FF, as well as ATF4, IL-6 and IL-8 mRNA expression in CCs, were significantly higher in group I follicles than group II. AGE treatment increased mRNA expression of ATF4, IL-6 and IL-8 in cultured GLCs. Knockdown of ATF4 abrogated the stimulatory effects of AGE on mRNA expression and protein secretion of IL-6 and IL-8. Our findings support the idea that accumulation of AGEs in follicles reduces oocyte competence by triggering inflammation via activation of ATF4 in the follicular microenvironment.